Should we give up on global governance? - Jean Pisani-Ferry (Bruegel, 2018)
The high point of global governance was reached in the mid-1990s around the creation of the World Trade Organisation. It was hoped that globalisation would be buttressed by a system of global rules and a network of specialised global institutions. Two decades later these hopes have been dashed by a series of global governance setbacks, the rise of economic nationalism and the dramatic change of attitude of the United States administration. From trade to the environment, a retreat from multilateralism is observable. The 2008 elevation of the G20 to leaders' level was an exception to this trend. But the G20 is no more than a political steering body. The reasons for this retreat partially arise from political developments in individual countries. But such factors hide series specific roadblocks to global governance: the growing number and diversity of countries involved; the mounting rivalry between the US and China; doubts about globalisation and the distribution of the associated benefits; the obsolescence of global rules and institutions; imbalances within the global governance regime; and increased complexity. What, then, should be the way forward? The demand for global governance has not diminished, but support for binding multilateral arrangements has. There is a need for alternative governance technologies that better accommodate the diversity of players, provide for more flexibility and rely less on compulsion. From competition to financial regulation, such arrangements have been developed in a series of fields already. They are often hailed as providing a solution to the governance conundrum. But their effectiveness should be assessed critically. Can they overcome the free-rider curse and enforcement problems? Usual game theory suggests not. Not all games are similar, however, and some collective action problems can be tackled without recourse to coercion. Against this background, multilateralists hesitate over the choice of a strategy. One option would be to seek to preserve the existing order to the greatest extent possible. Its downside is that it does not address the underlying problems. An alternative option is to try to redesign international arrangements, putting the emphasis on flexibility and voluntary participation. Its downside is that it risks overlooking the intrinsic problems of international or global collective action. A potentially more promising approach would be to define the minimum conditions that the multilateral framework must fulfil to provide a strong-enough basis for flexible, variable-geometry and possibly informal arrangements. In the end, we should neither cultivate the nostalgia of yesterday's order nor invest our hopes in ineffective international cooperation. The narrow path ahead is to establish a sufficient, critical multilateral base for flexible arrangements and to equip policymakers with a precise toolkit for determining, on a field-by-field basis, the minimum requirements for effective collective action.
Keywords: 330